2019
DOI: 10.1101/598177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorimidate Derivatives of Acyclovir; Antiviral Activity Against Canine Parvovirus In Vitro

Abstract: Canine parvovirosis is a very transmissible, severe and often deadly infectious disease of dogs caused by Type II canine parvovirus (CPV-2). Recently shows that Parvoviruses are very resistant to Acyclovir which is often used for HSV Chemotherapy in humans and various virucidal purposes in animal diseases in veterinary clinics and animal housing facilities. If acquiescence with vaccination programs and with appropriate decontamination plans is guaranteed, there should be no continuous, nor common, CPV-2 outbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Recently, another antivital drug, Acyclovir, guanine analogue commonly used to treat herpes simplex virus infection, have been shown to improve the disease conditions [98]. Further, an in-vitro study on A72 cell line showed that 9-(2-hydroxyethomethyl) guanine phosphoromonomorpholidate (ACV PMMPD), a phosphorimidate analogue of acyclovir inhibits CPV-2 replication with exhibiting 50% inhibitory concentrations (IC50s) in the low-micromolar range (50 μM) [99]. Recently, broadspectrum anti-CPV activity of some anti-parasitic drugs such as Nitazoxanide, Closantel Sodium, and Closantel have also been shown using F81 cells [100].…”
Section: Antiviral Drugsmentioning
confidence: 99%
“…Recently, another antivital drug, Acyclovir, guanine analogue commonly used to treat herpes simplex virus infection, have been shown to improve the disease conditions [98]. Further, an in-vitro study on A72 cell line showed that 9-(2-hydroxyethomethyl) guanine phosphoromonomorpholidate (ACV PMMPD), a phosphorimidate analogue of acyclovir inhibits CPV-2 replication with exhibiting 50% inhibitory concentrations (IC50s) in the low-micromolar range (50 μM) [99]. Recently, broadspectrum anti-CPV activity of some anti-parasitic drugs such as Nitazoxanide, Closantel Sodium, and Closantel have also been shown using F81 cells [100].…”
Section: Antiviral Drugsmentioning
confidence: 99%